The Impact of Daytime Sleepiness on Dietary Intake in Overweight/Obese Individuals with Diabetes and Chronic Kidney Disease (P08-019-19). (24th October 2019) - Woolf, Kathleen; Seixas, Azizi; Moore, Alexis; Popp, Collin; Coleman, William; Li, Huilin; Williams, Stephen; Goldfarb, David; Katz, Stuart; Sevick, Mary Ann
Abstract: Objectives: Sleep disturbances have been recognized as risk factors in the etiology of chronic disease and obesity. Although multifactorial, the link may be due to dietary intake, mediated by appetite hormones, hedonic feeding, altered intake times, and extended intake hours. The purpose of this study was to examine daytime sleepiness and dietary intake in overweight/obese individuals with diabetes and chronic kidney disease. Methods: Three-day food records were completed at baseline from 133 participants in an ongoing lifestyle intervention study, and analyzed using the Nutrition Data System for Research (2014). Daily dietary intakes were summarized for energy (kcal), carbohydrate (g), fat (g), alcohol (g), added sugars (g), and refined grains (ounce equivalents). Self-reported measures of daytime sleepiness were measured using the Epworth Sleepiness Scale (ESS). Participants rated their level of sleepiness (scale 0–3) in eight different situations, which were summed to provide a total score. The ESS scores were dichotomized with 0–10 indicating "normal daytime sleepiness" (NDS) and 11–24 indicating "excessive daytime sleepiness" (EDS). IBM SPSS Statistics (version 25.0) was utilized to complete the descriptive and inferential analyses. Independent sample t-tests examined differences between the two sleepiness groups. Results were considered significant at p ≤ 0.05. Results: The participants were 53.4% male, 89.5% non-Hispanic, 65.4% white, and 65.0 ± 9.4SD years of age with a mean body mass index of 34.0 ± 5.1SD kg/m 2 . Although there were no differences between sleepiness groups for fat and alcohol intakes, the EDS group reported a higher mean intake of carbohydrate (EDS: 247 ± 148SD g, NDS: 183 ± 76SD g; P = 0.048) and refined grains (EDS: 7.0 ± 6.5SD ounce, NDS: 4.2 ± 3.0SD ounce; P = 0.048). Although not statistically significant, the EDS group exhibited a trend toward having a higher energy intake (EDS: 2130 ± 1083SD kcal, NDS: 1776 ± 618SD kcal; P = 0.133) and added sugar intake (EDS: 44 ± 53SD g, NDS: 28 ± 26SD g, P = 0.179). Conclusions: Similar to other reports, sleep disturbances, as noted by EDS, were associated with a higher intake of carbohydrate and refined grains. The results of this study support the role of sleep, alongside diet and physical activity, as important modifiable risk factors for chronic disease and obesity. Funding Sources: National Institutes of Health (NIDDK, NINR)